Moving Forward, Looking Back: Taking Canadian Feminist Histories Online - Cattapan, Alana; DuPont, Quinn (Atlantis)

(untitled) (Mount Saint Vincent University, 2016)
Canadian feminist histories have long been bound to the printed page, potentially eluding audiences online. This article investigates how feminist histories can be expanded beyond traditional paper-bound venues by adopting a form of scholarly production that we call the “networked model.” Drawing on digital humanities methods, we argue that this model enables greater alignment with feminist epistemologies and an improved capacity to reach new audiences.